Frontispiece: Approaching Dissolved Species in Ammonoacidic GaN Crystal Growth: A Combined Solution NMR and Computational Study. Issue 31 (2nd June 2020) - Becker, Peter; Wonglakhon, Tanakorn; Zahn, Dirk; Gudat, Dietrich; Niewa, Rainer
Abstract : Superior GaN substrates for lightning applications are grown under ammonothermal conditions in high‐pressure autoclaves; however, chemical processes are still elusive. With NH4 Cl as mineralizer, hexamine gallium complexes with up to six surrounding chloride ions were identified to represent the dissolved species from NMR investigations at ambient temperature and under autogenous pressure of ammonia in combination with quantum mechanical calculations and molecular dynamics simulations. For more details see the Full Paper by P. Becker et al. on page 7008 ff.